Limnological Alterations on Lentic Environments Related to the conditions of the Watershed – Jacuí-Mirim river – RS - Kramer, Gisieli; Pereira Filho, Waterloo; Faccin, Carla Cargnin (Ciência e Natura, 2017)
On limnological studies, the influence of terrestrial environments and the meteorological conditions have been altering the natural characteristics of the optically active elements of water. Facing this problem, the following study proposes to identify, analyze and gather evidences supporting the variation on TSS concentration, pH and CE on the watershed of the Jacuí-Mirim River, RS, Brazil. The limnological collections were performed in October 2009, on three sample stations located on the site of study. The data collected on site and in the laboratory were interpreted and complemented with information of other works done on the same field of study. It was observed that the alterations of the natural characteristics caused on the aquatic environment evolve due to a variety of on influences, mainly on predominantly rural areas. Such finding was evident because of expressive values found for TSS concentration (maximum of 14 mg/L). It is believed the highest value of pH (7.5) is due to the influence of sediments deriving from farmable soils that use limestone for correction. The CE presented good conditions (maximum of 26.9 μS /cm). However, it is needed to constantly verify pH, CE and other parameters of analysis in order to achieve a more precise conclusion.